ProBNP, cytokines, and the Nrf2/HO-1 signaling pathway A cross-sectional study on cardiovascular risk in rheumatoid arthritis - Nobre, Christiane Aguiar (Clinical immunology (Orlando, Fla.), 2025)
Copyright © 2025 Elsevier Inc. All rights reserved.